(untitled) (The Pakistan Development Review, 1994)
Women in South Asia comprise close to one third of the world’s female population. Not only is South Asia an extremely populous region but population growth rates have been much higher than averages for other developing countries. The implications of high population growth rates are quite direct and severe for women, as they are the result of high levels of fertility which have prevailed for some time in this region. The stable and high levels of fertility along with falling mortality have led to a youthful population structure where about 45 percent of the population is aged under 15. Since childbearing as well as childrearing are almost the sole responsibility of women, these figures reflect the burden of high fertility amongst South Asian women. An average South Asian woman marries at a fairly young age, (even though the region is exhibiting a distinct trend of rising age at marriage for females) and starts bearing children soon after. Though fertility rates have been declining in most of India and Bangladesh while they had already reached quite low levels in Sri Lanka, other countries of the region (mainly Nepal and Pakistan) have still to experience any dramatic declines in fertility. In contrast with trends in the Latin American and South East Asian region, increases in contraceptive use in South Asia have not played as substantive a role in fertility declines as changing marriage patterns, atleast so far. See Table 1 for recent figures on fertility and contraceptive use among females of this region.